METODE WETONAN (MANGAJI TUDANG) SEBAGAI MEDIA BERDAKWAH K.H.ABDURRAHMAN AMBO DALLE DI PONDOK PESANTREN DDI MANGKOSO - Iskandar Iskandar; Faten hamama; Abd Rahim Arsyad (KOMUNIDA : Media Komunikasi dan Dakwah, 2016)
Da'wah is an activity performed by an individual or group of individuals or groups that contain an invitation or call to do so ma'ruf and forbidding the creation of a happy life in this world and in the hereafter. One of the media propaganda that is often done by K.H.Abdurrahman Ambo Dalle is a method wetonan (mangaji Tudang). Wetonan method (mangaji Tudang) is performed at recitals book dimasjid at boarding DDI Mangkoso. The author uses descriptive qualitative research methods in collecting data used method of observation draft interview. Mechanical sampling interviewed, didiasarkan the sampling group with the identification of social groupings associated with this research. The results of the study, researchers obtained data is that the method wetonan formerly performed by K.H.Abdurrahman Ambo Dalle boarding school when he founded DDI Mangkoso still used up to now in Bugis is also called the mangaji Tudang. Application of this method as a means of preaching wetonan K.H.Abdurrahman Ambo Dalle has been modified from the process of reading and translating the yellow book do perkata by mentioning the meaning of the word and the position of each word of the nahwu and sharf. Application of the method wetonan (mangaji Tudang) in enhancing science students in religious matters supported by a qualified teacher competence. Facilities and infrastructure has been adequate. And also viewed in terms of benefit is so great that the method is still used today.